The genome sequence of a drosophilid fruit fly, Drosophila histrio (Meigen, 1830) [version 1; peer review: 2 approved] - Darren J. Obbard (Wellcome Open Research, 2024)
We present a genome assembly from an individual female Drosophila histrio (the drosophilid fruit fly; Arthropoda; Insecta; Diptera; Drosophilidae). The genome sequence is 189.2 megabases in span. Most of the assembly is scaffolded into 5 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 16.02 kilobases in length.